Innovations in digital comics : a popular revolution - Benatti, Francesca (Cambridge elements. Elements in publishing and book culture, 2024)
The success of popular webcomics (comics produced and read entirely digitally) is the greatest revolution in the comics medium of the last two decades. Webcomics exploit a socio-technical convergence between digital platforms and participatory cultures, enabling global authors to work together with global audiences to transcend established print comics structures. After defining digital comics, webcomics and webtoons, this Element presents a case study of Korean platform WEBTOON, which achieved 100 billion global page views in 2019. The study analyses data from their website, including views, subscriptions and likes, to quantify and assess whether WEBTOON's commercial and critical success is connected to its inclusion of a wider range of genres and of a more diverse author base than mainstream English-language print comics. In so doing, it performs the first Book Historical study of webcomics and webtoons. This title is also available as Open Access on Cambridge Core.